Pengaruh Kualitas Pelayanan Dan Kepercayaan Terhadap Loyalitas Pelanggan Dengan Kepuasan Pelanggan Sebagai Variabel Intervening - Christina Dewi W; Apriana Anggreini Bangun; Ratna Susilowati; Mughni Mutmainnah Iskandar A (ARBITRASE: Journal of Economics and Accounting, 2023)
This research was conducted with the aim of analyzing the influence of service quality and trust on customer loyalty with satisfaction as an intervening variable for JNE customers in Jakarta. The sampling technique used in this research is non-probability sampling. The criteria for respondents are by distributing questionnaires via Google Form to 100 respondents who are JNE customers who are at least 17 years old and live in the city of Jakarta. The analysis technique used is path. The research results show that Service Quality partially has no effect on Customer Loyalty, that the Service Quality variable produces a t count of 0.329 <1.984 with a significance level of 0.743. Trust partially influences Customer Loyalty, that the Trust variable produces a t count of 3.198> 1.984 with a significance level of 0.002. Satisfaction partially influences Customer Loyalty, that the Customer Satisfaction variable produces a t count of 4.621>1.984 with a significance level of 0.000. Service Quality partially has no effect on Customer Satisfaction, that the Customer Satisfaction variable produces a t count of 1.224<1.984 with a significance level of 0.030. Trust partially influences Customer Satisfaction, that the Trust variable produces a t count of 6.359>1.984 with a significance level of 0.000.